ENERGY OF SUGGESTION - Teplan, Dusan (Bohemica Olomucensia, 2021)
The aim of the study is to present the course and basic conditions of the reception of Viktor Shklovsky's work in Slovakia. His works in the field of literary theory had a significant influence on the development of modern Slovak literary theory. Gradually, the public became acquainted with his literary work and his work in the field of film theory. However, as a representative of Russian formalism, he was rejected and banned in times of authoritarian political regimes. In the study we show what the response to his work was and what results he led to.
Keywords: Viktor Shklovsky; Slovakia; literature; reception; structuralism; formalism; translation